(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
This study investigated the role of Six Sigma in Hospitality Industry specifically hotel sector, and how Six Sigma- DMAIC business model (Define, Measure, Analyze, Improve, and Control) has been adopted in the hotel business operations to bring the positive business results for example defining the problem-D, measuring the problem-M, analyzing data to explore the source of the problem-A (analysis of defects in a particular hotel operation process), improving the performance-I to eliminate the source of faults and controlling-processes-(C) to avoid the continuous problematic-monitoring the improvement within the particular hotel. Also, this article exposes how Six Sigma methodology can be used: in developing a business strategy, in developing a business Vision, in developing business Benchmark, in developing business Goal, in establishing a business Statistical Measure, and establishing a Robust Methodology throughout the hotel business operation. The theory employed in this article is constructivism theory that align together with the historical development of the idea of Six Sigma idea (MAIC) as developed by Smith in 1986 then later DMAIC as added by Welch in 2000. The result shows that the hotels which applied Six Sigma, the performance of the particular hotel were improved.